Tensile, flow and thermal properties of biodegradable PLA/pineapple fiber composite: article - Mohamed, Hadi Faiz; Sharudin, Rahida Wati; Mohamed, Rahmah (2019)
Human activities and food need to be pack than be transported to the worldwide especially in import export business. The materials that use was very important and had their own shelf-life to deliver most products in its required condition a specification. In reinforcement the strength of various regulations that used to aim at reducing the wastes generated, packaging waste forms main municipal solid waste and this will cause increasing in environmental problems. With regard to environment aspects, it would be beneficial if natural fibers could be used instead of synthetic fibers as reinforcement in some structural and food packaging applications. There were many things need to be consider during fibers selection such as length, strength, and purpose of usage. Raw material for production of PHA is us a pineapple leaf fibers (PALF). Different composition that used in fabrication of PLA and PALF which were 50% PLA - 50%PALF, 60% PLA – 40% PALF and 100% PLA – 0% PALF for controlled. There were four testing need to be done which were melt flow tester, tensile tester, Fourier Transform Infrared (FTIR) and Differential Scanning Calorimetry (DSC).